The Engineered Chloroplast Genome Just Got Smarter. (October 2015) - Jin, Shuangxia; Daniell, Henry
<x xml:space="preserve">Abstract</x> Chloroplasts are known to sustain life on earth by providing food, fuel, and oxygen through the process of photosynthesis. However, the chloroplast genome has also been smartly engineered to confer valuable agronomic traits and/or serve as bioreactors for the production of industrial enzymes, biopharmaceuticals, bioproducts, or vaccines. The recent breakthrough in hyperexpression of biopharmaceuticals in edible leaves has facilitated progression to clinical studies by major pharmaceutical companies. This review critically evaluates progress in developing new tools to enhance or simplify expression of targeted genes in chloroplasts. These tools hold the promise to further the development of novel fuels and products, enhance the photosynthetic process, and increase our understanding of retrograde signaling and cellular processes.